Efektifitas Pijat Postpartum dengan Korset Pijat terhadap Kecepatan Pengeluaran ASI Ibu Postpartum - K Kasmiati; Andi Ria Metasari; E Ermawati (Jurnal Ilmiah Kesehatan, 2022)
Fulfillment of nutrition in newborns is very important. However, there are many things that become obstacles for postpartum mothers in terms of breastfeeding at the beginning of the birth period, such as fatigue in postpartum mothers, inability to breastfeed, lack of knowledge that thinks the existing milk is not enough to meet the needs of their babies. This study aims to see the effectiveness of the massage corset on the speed of milk production. This research was conducted using a cross sectional experimental study method with the application of postpartum massage using a massage corset. This research was conducted in 2 places, namely the Independent Practice of Midwife HJ.Harfiani and Independent Practice of Midwife Jumiani for 4 months. This study shows that the application of postpartum massage using a massage corset has a good effectiveness in accelerating the expulsion of breast milk from 20 samples, 17 people (85%) experienced rapid milk expulsion, 3 people (15%), while those who were not massaged from 20 samples with fast discharge were 5 people (25%) and 15 people were slow spending (75%). The results of the T-test showed that the massage corset was effective in accelerating the expulsion of breast milk in postpartum mothers. So that the results of this study can be an additional alternative for postpartum mothers in providing a sense of comfort and accelerating breastfeeding for postpartum mothers.